Implementation of Circular Economy Practices in Sustainable Business Models: Evidence from a Home-Based Convection Industry - Dharmawan P Hadad; Noviarti; Yuli Setiawan; Teguh Rifandi (LP2M IAIN Palopo, 2026)
This study aims to analyze the implementation of circular economy practices in a home-based convection industry and examine their contribution to sustainable business development and the promotion of green lifestyles within the surrounding community. Methods: This study employs a qualitative research approach with a case study design focusing on Konveksi Mande. Data were collected through in-depth interviews, observation, and documentation involving key informants, operational employees, and community members. The data were analyzed using qualitative techniques, including data reduction, data display, and conclusion drawing. Results: The findings indicate that circular economy practices have been implemented through the 5R principles, namely reduce, reuse, recycle, recovery, and repair, although the level of implementation varies. The reduce principle is strongly applied through material efficiency and production control, while reuse, recycle, and recovery are implemented at a moderate level through waste collection and collaboration with external parties. However, the repair principle has not yet been implemented, indicating limitations in internal innovation capabilities. The implementation of these practices contributes to environmental sustainability by reducing textile waste, generating economic benefits through additional income, and enhancing social awareness by encouraging green lifestyle adoption. Implications: This study provides practical implications that SMEs can adopt simple and feasible circular economy practices to support sustainability and contribute to the literature by highlighting the role of small-scale industries in promoting circular economy and green lifestyles. Future research is recommended to explore innovation strategies and apply quantitative approaches to strengthen the generalizability of findings.